PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN DENGAN MENGGUNAKAN MODEL PEMBELAJARAN TALKING STICK PADA SISWA KELAS VI SD - Efriwati, Efriwati (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This action research aimed to describe the improving of skill of comprehension reading by using the learning models of talking stick. The subject of this research is teacher and students of grade six at elementary school 03 Alai. The approach used was a qualitative and quantitative. The learning activities were before reading, during reading, and after reading activity. The result showed an increase in students learning outcomes at first cycle was 53%, but in the second cycle went up to 94%.   Kata Kunci; membaca pemahaman; model talking stick